Integración temporal explícita con grandes pasos de tiempo de la ecuación de transmisión del calor - Becker, Pablo Javier (2012)
We present a novel fully explicit time integration method that remains stable for large time steps, requires neither matrix inversions nor solving a system of equations and therefore allows for nearly effort-less parallelization. In this first paper the proposed approach is applied to solve conduction heat transfer problems, showing that it is stable for any time step as is the case with implicit methods but with a much lower computation time.